Application of Six Sigma management in prevention of central venous catheter-related bloodstream infection in children with liver transplantation (六西格玛管理在预防肝移植儿童中心静脉导管相关性血流感染中的应用) - DI Mengxue (邸梦雪); MA Huanhuan (马欢欢); JIANG Ying (蒋莹); DONG Huan (董环); GAO Wei (高伟) (Journal of International Translational Medicine Limited, 2024)
Objective To investigate the effect of Six Sigma management in prevention of central venous catheter-related bloodstream infections (CLABSI) in children undergoing liver transplantation. Methods From January to September 2021, a total of 216 children with central venous catheter placement were selected as the control group, and 192 children with central venous catheter indwelling from January to September 2022 were selected as the intervention group. The control group received routine nursing management in the maintenance of central venous catheters, while the intervention group adopted Six Sigma management on the basis of routine care measures. The incidence of CLABSI and 1000-day catheter infection rate were compared between the two groups. Results The incidence of CLABSI in the intervention group was 1. 04%, which was lower than 1. 39% in the control group (P＜0. 05). The 1000-day catheter infection rate was 0. 64 ‰ in the intervention group, which was lower than 1. 07 ‰ in the control group (P＜0. 05). Conclusion The Six Sigma management method can effectively reduce the incidence of CLABSI in children undergoing liver transplantation and improve their safety. (目的 探讨六西格玛管理方法在预防肝移植儿童中心静脉导管相关性血流感染(CLABSI)中的应用效果。方法 选取2021年1月-9月留置中心静脉导管的216例患儿为对照组, 2022年1月-9月留置中心静脉导管192例患儿为干预组。针对肝移植儿童中心静脉导管的维护管理, 对照组实施常规护理措施, 干预组在对照组基础上采用六西格玛管理法。对比两组的CLABSI的发生率及千日导管血流感染率。结果 干预组CLABSI发生率为1. 04%, 低于对照组的1. 39%。差异有统计学意义(P＜0. 05); 干预组千日导管血流感染率为0. 64‰, 低于对照组1. 07‰, 差异有统计学意义(P＜0. 05)。结论 西格玛管理方法能有效降低肝移植儿童CLABSI发生率, 提高患儿安全。)